Entrepreneurial and Technical Capability in Relation to Productivity: Basis for Resource Generation Development Plan - Cadiz, Sally (JPAIR Multidisciplinary Research, 2012)
This study determined the entrepreneurial and technical capability of Carlos Hilado Memorial State College in relation to productivity, basis for the formulation of Resource Generation Development Plan. The researcher- made questionnaire was based from the Entrepreneurial Capability Indicator Questionnaire 2005 conducted to 150 CHMSC faculty members of the four campuses. Descriptive Method was used to determine the profile and responses on entrepreneurial and technical capability of the college.T-test and ANOVA were used as inferential statistical tools. Entrepreneurial and technical capability of the faculty members was to a moderate extent. Productivity capability was low extent. No significant differences were noted in the level of perception of faculty members in terms of Entrepreneurial, Technical and Productivity Capability when grouped according to different variables. The acquisition, utilization and production aspects be allocated to capital investment for sustainable programs and projects developed by the faculty members. The faculty members have to formulate one project proposal per semester for the resource generation development plan of the college.